Dairy farmer policy preferences - Wolf, Christopher A.; Tonsor, Glynn T. (My University, 2014)
Dairy policy often becomes a contentious topic during U.S. farm bill negotiations. The dairy subtitle of the 2012 farm bill has been debated and discussed since 2009. This research uses best-worst scenario methods to analyze dairy farmer preferences for policy options, including eliminating existing dairy policies, implementing new dairy policies related to income support and growth management, and ending ethanol subsidies. Results indicate that large and small dairy herd operators have differing preferences. Large herd operators prefer to end ethanol subsidies rather than specific dairy policy changes, while small herd operators most preferred support for income over feed-cost margins.
Keywords: Best-worst scaling; Dairy policy; Farm bill; Farmer preferences; Herd size